2007
DOI: 10.1016/j.jmoneco.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and inequality

Abstract: Crosscountry evidence on inflation and income inequality suggests that they are positively correlated. I explore the hypothesis that this correlation is the outcome of a distributional conflict underlying the determination of fiscal policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
222
1
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(268 citation statements)
references
References 31 publications
24
222
1
21
Order By: Relevance
“…Financial depth has a positive income-redistributive effect in Africa: consistent with Kai & Hamori (2009). High inflation (above 117% in the mean from Appendix 1) fuels inequality, in line with Albanesi (2007). Trade openness has a negative income-redistributive effect for a significant part of the African continent (Kai & Hamori, 2009).…”
Section: Resultsmentioning
confidence: 94%
“…Financial depth has a positive income-redistributive effect in Africa: consistent with Kai & Hamori (2009). High inflation (above 117% in the mean from Appendix 1) fuels inequality, in line with Albanesi (2007). Trade openness has a negative income-redistributive effect for a significant part of the African continent (Kai & Hamori, 2009).…”
Section: Resultsmentioning
confidence: 94%
“…Also, while low inflation may mitigate inequality (Bulir, 1998;Lopez, 2004), high inflation has been documented to have a negative income redistributive effect (Albanesi, 2007) in recent African inequality literature (Asongu, 2012f Notes. Dependent variable is the GDP per capita growth rate.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Easterly and Fisher (2001) found that high price inflation tends to lower the share of the bottom quintile and the real minimum wage increasing income inequality, and that the poor are more likely than the rich to mention price inflation as a central economic concern. Similarly, several other works -such as Bulir (2001) or Albanesi (2007) -presented evidence of correlating high rates of price inflation with income inequality, poverty, or both.…”
mentioning
confidence: 78%